TYPES OF PERSONAL LETTERS IN “SLAVENOBOLGARSKIY PREDRUCHNIY POSLATELNIK ZA NASTAVLENIЕ NA BOLGARSKITE YUNOSHI” (1835) BY NEOPHYTE BOZVELI AND EMANUIL VASKIDOVICH - Maria Mitskova (Езиков свят, 2023)
The present article explores the teaching dedicated to the different personal letter types presented in one of the first printed letter-writing manuals – “Slavenobolgarskiy Predruchniy Poslatelnik za Nastavlenia na Bolgarskite Yunoshi“ (1835) by Neophyte Bozveli and Emanuil Vaskidovich. The educational goals of the book transpire in the very essence of the idea that the epistolary theory should be implemented into clear examples. Therefore, types of letter patterns were provided not for mere reproducing but for interpretation and implication. And it is not a coincidence that by including the largest possible collection of examples of human relations – written and used as images of the various aspects of the human connections and interactions – Bozveli and Vaskidovich brought forward their practical epistolary lessons on writing good letters and maintaining a correspondence and etiquette. The themes of the personal letters and fictional stories chosen by the co-authors not only reveal the wide range of possible human relations inside immediate and friend circles but also extol social, civil, and moral virtues. The alluded ethical issues of love, respect, commitment, filial love, clear conscience, kindness, and sincerity, as well as the influence they have or aim to have both on the sender and the addressee, implicitly point out the principles of good behavior at home, at school, and on the street. They truly embody the enlightenment philosophy about the new ethics – moral education, the core value of which is to work for the benefit of society.